2017
DOI: 10.1242/dev.147033
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Atg16 promotes enteroendocrine cell differentiation via regulation of intestinal Slit/Robo signaling

Abstract: Genetic variations of Atg16l1, Slit2 and Rab19 predispose to the development of inflammatory bowel disease (IBD), but the relationship between these mutations is unclear. Here we show that in Drosophila guts lacking the WD40 domain of Atg16, pre-enteroendocrine (pre-EE) cells accumulate that fail to differentiate into properly functioning secretory EE cells. Mechanistically, loss of Atg16 or its binding partner Rab19 impairs Slit production, which normally inhibits EE cell generation by activating Robo signali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 61 publications
0
24
0
1
Order By: Relevance
“…Interestingly, L. dispar autophagy-related protein 16 (Atg16; Atg16L1 in mammals) was one of 11 DEGs up-regulated after VSV infection that was not up-regulated after VACV coinfection (Dataset S6). Autophagy is a conserved cellular process in which cytosolic components are degraded after targeting to lipid-enclosed vesicles termed "autophagosomes" (63)(64)(65). Fusion of autophagosomes with lysosomes results in the degradation of the membrane-enclosed material and this process requires Atg16 (64).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, L. dispar autophagy-related protein 16 (Atg16; Atg16L1 in mammals) was one of 11 DEGs up-regulated after VSV infection that was not up-regulated after VACV coinfection (Dataset S6). Autophagy is a conserved cellular process in which cytosolic components are degraded after targeting to lipid-enclosed vesicles termed "autophagosomes" (63)(64)(65). Fusion of autophagosomes with lysosomes results in the degradation of the membrane-enclosed material and this process requires Atg16 (64).…”
Section: Resultsmentioning
confidence: 99%
“…Autophagy is a conserved cellular process in which cytosolic components are degraded after targeting to lipid-enclosed vesicles termed "autophagosomes" (63)(64)(65). Fusion of autophagosomes with lysosomes results in the degradation of the membrane-enclosed material and this process requires Atg16 (64). Studies in Drosophila have shown that VSV infection induces autophagosome formation and that autophagy contributes to the restriction of VSV (66).…”
Section: Resultsmentioning
confidence: 99%
“…In Drosophila, ATG16 is crucial for the differentiation of intestinal stem cells into enteroendocrine (EE) cells. Expression of ATG16 lacking the WD40 repeat domain led to morphological changes in the intestine that resembled inflammatory bowel disease (Nagy et al, 2017). Furthermore, the C-terminal WD40 domain is important in xenophagy (Xiong et al, 2019).…”
Section: Further Autophagy-independent Functions Of Atg5 Atg12 and Amentioning
confidence: 99%
“…For instance, autophagy‐related gene FIP200 plays a vital role in the maintenance and differentiation of postnatal neural stem cells, and its deletion leads to accumulation of p62 in order to regulate the cell fate through activation of superoxide . Another gene, Atg16, plays a critical role in gut homeostasis and its mutation causes an impaired Slit/Robo‐dependent differentiation of the enteroendocrine cells to trigger inflammation, which may increase the risk of developing colorectal cancer . The autophagy factor UVRAG, present in the Beclin1/Vps34 complex, is mutated in several cancers, causing an abnormal left‐right axis formation, leading to heterotaxy .…”
Section: Introductionmentioning
confidence: 99%
“…15 Another gene, Atg16, plays a critical role in gut homeostasis and its mutation causes an impaired Slit/Robodependent differentiation of the enteroendocrine cells to trigger inflammation, which may increase the risk of developing colorectal cancer. 16 The autophagy factor UVRAG, present in the Beclin1/Vps34 complex, is mutated in several cancers, causing an abnormal left-right axis formation, leading to heterotaxy. 17 Furthermore, depletion of Beclin1 has been reported to inhibit both autophagy and differentiation capabilities.…”
mentioning
confidence: 99%